(untitled) (Perner’s Contacts, 2012)
The presented article focuses on characteristics of automotive supply chain. The theoretical part provides an overview of component suppliers’ structure. Next part is relating to supply chain base in Slovakia. There are also some actual trends in automotive and supply industry based on flexibility and agility principles. This factor is known as a competitive advantage in global automotive benchmark. The example of application build-to-order supply management is presented in condition of automotive plant with directly customers purchase impulses. At the close part of the paper is reason for the need of using support information technologies tools to flexible and efficient design of suppliers’ production and logistics processes